Highly efficient and automated isolation technology for extracellular vesicles microRNA - Di, Kaili; Fan, Boyue; Gu, Xinrui; Huang, Rongrong; Khan, Adeel; Liu, Chang; Shen, Han; Li, Zhiyang (Frontiers in Bioengineering and Biotechnology, 2022)
MicroRNA (miRNA) in extracellular vesicles (EVs) has great potential to be a promising marker in liquid biopsy. However, the present EVs isolation methods, such as ultracentrifugation have complicated and long-time operation, which impede research on EVs miRNA. The downstream complex miRNA extraction process will also greatly increase the detection cycle and loss. We firstly established a simple automated technique to efficiently extract target miRNAs in EVs from plasma based on Fe3O4@TiO2 beads with high affinity and capture efficiency. We combined heat-lysis method for quick and simple EVs miRNA extraction and detection. Results indicated that our method has more RNA yield than TRIzol or commercial kit and could completed EVs enrichment and miRNA extraction in 30 min. Through the detection of miRNA-21, healthy people and lung cancer patients were distinguished, which verified the possibility of the application in clinical detection. The automated isolation technology for EVs miRNA has good repeatability and high throughput, with great application potential in clinical diagnosis.